High ratio of monocytes to high-density lipoprotein is associated with hemorrhagic transformation in acute ischemic stroke patients on intravenous thrombolysis - Xia, Lingfan; Xu, Tong; Zhan, Zhenxiang; Wu, Yucong; Xu, Ye; Cao, Yungang; Han, Zhao (Frontiers in Aging Neuroscience, 2022)
Background Hemorrhagic transformation (HT) is a frequent, serious complication in acute ischemic stroke patients on intravenous thrombolysis. Here we investigated whether risk of HT is associated with the ratio of monocyte count to high-density lipoprotein level (MHR). Materials and methods Medical records were retrospectively examined for consecutive patients with acute ischemic stroke who received thrombolytic therapy. HT was diagnosed by computed tomography at 24–36 h after therapy. Potential association between MHR and HT was examined using logistic regression. Results A total of 340 patients were analyzed, and their median MHR was 0.44 (0.31–0.59). MHR was higher in the 51 patients (15.0%) with HT than in those who did not suffer HT (0.53 vs. 0.42, P = 0.001). Multivariate logistic regression showed that, after adjusting for potential confounders, MHR was an independent risk factor for HT (OR 7.50, 95% CI 1.64 to 34.35, P = 0.009). Risk of HT was significantly higher among patients whose MHR fell in the third quartile (0.42–0.53) and the fourth quartile (> 0.53) than among those with MHR in the first quartile (< 0.31; OR 3.53, 95% CI 1.11 to 11.20, P = 0.032; OR 4.79, 95% CI 1.49 to 15.42, P = 0.009). Conclusion High MHR may be independently associated with higher risk of HT in patients with acute ischemic stroke on intravenous thrombolysis.